IMAGING DIAGNOSIS OF DISC HERNIATION - CASE REPORT - Torres Reis, Letícia; Almeida de Oliveira, Martha (Journal of Interdisciplinary Debates, 2023)
This is a clinical case report of a Dachshund dog, known for having a more prone spinal column to health problems such as herniated discs, due to its long and low body. The animal was taken to the veterinarian for presenting difficulty in gait and avoiding putting the left front paw on the ground. A computed tomography was performed, which revealed the presence of herniated discs in various regions of the dog’s spinal column. Initially, medication treatment was prescribed, but as the animal presented paralysis in the front legs and side effects due to the long period of use of pain control medication, surgical intervention was necessary. Physiotherapy was recommended to assist in the animal’s recovery.